2009
DOI: 10.1142/s0217984909020928
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Bulk Metallic Glasses at Cryogenic Temperatures

Abstract: Metallic glasses (amorphous alloys) consist of atomic clusters, interconnecting zones and free volume. The atomic clusters are connected together, resulting in the formation of a rigid skeleton through the interconnecting zones. Some metallic glasses even contain crystalline structures at the nanoscale. Even though there is supposed to be no structural change at temperatures below the glass transition temperature, metallic glasses exhibit different mechanical behaviors at cryogenic temperatures. Contrary to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…They found the number and stability of amorphous phases increased with the increase of nitrogen content. In the study by Fan et al [153] mentioned above, the microhardness of the Fe-based amorphous alloy decreases with increasing nitrogen content, as shown in Figure 22b. Therefore, reducing the surface hardness of Fe-based amorphous alloys through a nitrogen atmosphere and enhancing the stability of its amorphous phase is helpful for diamond tools to better machine the surface layer of workpieces with reduced hardness.…”
Section: Fe-based Amorphous Alloys At Low Temperaturementioning
confidence: 70%
See 1 more Smart Citation
“…They found the number and stability of amorphous phases increased with the increase of nitrogen content. In the study by Fan et al [153] mentioned above, the microhardness of the Fe-based amorphous alloy decreases with increasing nitrogen content, as shown in Figure 22b. Therefore, reducing the surface hardness of Fe-based amorphous alloys through a nitrogen atmosphere and enhancing the stability of its amorphous phase is helpful for diamond tools to better machine the surface layer of workpieces with reduced hardness.…”
Section: Fe-based Amorphous Alloys At Low Temperaturementioning
confidence: 70%
“…Jin et al [152] concluded that proper deep cooling treatment of Fe-based amorphous alloy coatings can reduce the porosity, and the wear resistance of Fe-based amorphous alloy coatings gradually increases with longer deep cooling treatment time. Based on the excellent properties exhibited by amorphous alloys at low temperatures, Fan et al [153] investigated in more depth which amorphous alloys can be benefited by low temperatures and which amorphous alloys are not. They showed that at low temperatures, although the structure of amorphous alloys does not change, amorphous alloys exhibit different mechanical behavior, and in contrast to crystalline materials, the strength and ductility of some amorphous alloys increase significantly with decreasing temperatures in the low-temperature range, such as Ni-and Ni-Fe-based amorphous ribbons.…”
Section: Fe-based Amorphous Alloys At Low Temperaturementioning
confidence: 99%
“…Different from the traditional alloys, bulk metallic glasses (BMGs) are amorphous alloys, which have random atomic arrangement without crystalline defects due to rapid cooling from the liquid to the solid state. Due to their unique amorphous structure and the absence of crystalline defects, BMGs not only have excellent mechanical properties but also possess the viscous flow behavior like polymers in the supercooled liquid region (SCLR), which is above the glass-transition temperature and below the crystallization temperature. This viscous flow behavior could be utilized for thermal imprinting. , Although the metallic glass was first made in 1960, the thin film metallic glasses (TFMGs) were not fabricated until 1980s. Compared with the liquid-to-solid fabrication process of BMGs, the vapor-to-solid process of TFMGs by physical vapor deposition provides a much faster cooling rate which, in turn, would result in the better glass forming ability and the wider composition range for TFMGs. , Therefore, TFMGs not only retain the unique properties of BMGs but also are more flexible in compositions to maintain the amorphous structure.…”
Section: Introductionmentioning
confidence: 99%
“…at 77 K), just the opposite of usual behaviour. It is widely observed 12 that in compression a MG that fails easily at room temperature (RT) can have large plastic strain (ϵ P ) at low temperature (LT, e.g. 77 K), e.g.…”
Section: Introductionmentioning
confidence: 99%